LANGUAGE LEARNING STRATEGIES USED BY THE STUDENTS IN LEARNING ENGLISH THROUGH ONLINE - Harry Sugiartha, Putu Angga; Supatra, P.E.D.; Hadisaputra, I.N.P. (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
The Covid-19 pandemic has made learning activities carried out online. Because of this situation, the teacher can also choose a reasonable and appropriate strategy in teaching students, especially in English. This has an impact on students' low English skills. This study aims to analyze the language learning strategies used by students while learning English online. This type of research is qualitative with a case study research design. The population in this study found 59 students. The sample in this study found 20 students. Data collection was done by observation and interview methods. This study uses two instruments, namely a checklist of observations and interview guidelines. This finding indicates that while learning English, students boldly use four types of language learning strategies, namely cognitive strategies, compensation strategies, metacognitive strategies, and social strategies. The use of language learning strategies in learning English online must be followed by the skills of the English teacher in teaching students. Therefore, teachers must support and facilitate students during online learning of English. The use of appropriate teaching media and learning materials will help students learn languages online.